(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Study was conducted to check the Brain Drain as an opportunity or Problem by using Remittances as the result of brain drain and economic variables of GDP, Per Capita Income, and Public Debt was used in the analysis to check the effect by using multiple regression which states that overall model is fit and independent variables are rightly predicting the dependent variables and concluded that brain drain proved to be an opportunity for the government of Pakistan for improving the economic position.